Pengembangan Wirausaha Masyarakat Peternak Domba di Wonosobo melalui Pelatihan Penyusunan Laporan Keuangan dan Pemasaran Digital - Luluk Muhimatul Ifada; Winarsih Winarsih; Olivia Fachrunnisa; Ardian Adhiatma; Hendar Hendar; Ken Sudarti (Jurnal Nusantara Mengabdi, 2023)
Purpose: This community service activity aims to improve and foster an entrepreneurial spirit in the surrounding community by providing an understanding of entrepreneurship, marketing and the preparation of financial reports. Methodology: The method for implementing community service activities is carried out in several stages. The first stage is the preparatory stage through observation and material preparation. The second stage is the implementation of activities in the form of technical guidance which is carried out by presenting material, practice of preparing financial reports and discussions. The third stage is an evaluation that aims to accommodate the problems faced by participants in compiling financial reports independently. Results: The results of community service for dombos breeders (Wonosobo sheep) participants understood how to prepare small and medium enterprises financial reports and began to have entrepreneurial and marketing knowledge. This is a good start to develop dombos farming in Wonosobo. The training went well and received a good response from the participants. Conclusion: This community service activity had a positive impact because participants ultimately had the skills and knowledge of digital marketing management and the preparation of financial reports. Through this community service activity, it is hoped that breeders can apply the knowledge they have acquired to develop the dombos business.